The Influence of Social Media Marketing on Investment in Sharia Capital Market - Evania Herindar; Alya Shabrina; Ricka Krisnawati (Ekonomi Islam Indonesia, 2021)
In the past few years, sharia investment rates in Indonesia has undergone massive growth. From the span of one year only, by 2017 to 2018 the sharia investment rates has risen to 92% (Peta Investor Syariah 2018). Nevertheless, the major growth has not been optimized entirely. It can be observed from the data of active sharia investor which only took 56% of the total amount of sharia investor. After thoroughly studied, Indonesia has a small *of financial inclusion and literation. A solution is needed for Indonesia society in order to be well literate, because a study has shown that financial literation has a positive and significant impact towards investment decision in sharia capital market which can be identified from the nominal of Sig. from financial literation in the amount of 0,041 < 0.05 (Muhammad Yusuf, 2018: 63). Research has proven that social media has a big impact in Indonesia, solely in 2019 Indonesia social media user has reached 150 billion or equivalent to 56% of the total population (Wearesosial Hootsuite). Therefore, social media marketing is expected to be a medium for increasing the rates of investment. This study aimed to see the impact of social media marketing on investment. Multiple linear regression is the method used in this study, and the type of study is explanatory research with a quantitative approach. The data sourced used is primary and secondary data with the sample withdrawal technique, purposive sampling. The conclusion from this study social media marketing (independent variable) has a positive and significant relation on sharia investment rates (dependent variable). Social media marketing provides a considerable impact on sharia investment.